2001
DOI: 10.1006/nimg.2001.0862
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Statistical Approach to Deformation-Based Morphometry

Abstract: We present a unified statistical framework for analyzing temporally varying brain morphology using the 3D displacement vector field from a nonlinear deformation required to register a subject's brain to an atlas brain. The unification comes from a single model for structural change, rather than two separate models, one for displacement and one for volume changes. The displacement velocity field rather than the displacement itself is used to set up a linear model to account for temporal variations. By introduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
308
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(318 citation statements)
references
References 31 publications
3
308
0
2
Order By: Relevance
“…Jacobian determinant values derived from these tensor fields indicate the fractional volume expansion and contraction at each voxel (e.g., Chung et al, 2001;Davatzikos et al, 1996). In other words, the resulting Jacobian map quantifies the magnitude of regional volume alterations required to match the template.…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Jacobian determinant values derived from these tensor fields indicate the fractional volume expansion and contraction at each voxel (e.g., Chung et al, 2001;Davatzikos et al, 1996). In other words, the resulting Jacobian map quantifies the magnitude of regional volume alterations required to match the template.…”
Section: Image Analysismentioning
confidence: 99%
“…Compared to prior VBM studies, the following methodological improvements have been made in the current study. First, tensor-based morphometry (TBM; Ashburner et al, 1998;Chung et al, 2001;Davatzikos, Genc, Xu, & Resnick, 2001;Gaser, Volz, Kiebel, Riehemann, & Sauer, 1999;Studholme et al, 2004;Thompson et al, 2000) was used. TBM methods utilize information from high resolution deformation tensor fields obtained from the non-linear transformations of individual images to the template.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, deformation-based morphometry and tensor-based morphometry in the normal developmental studies in children show that there is relative brain tissue growth in the corpus callosum over time (Chung et al, 2001;Thompson et al, 2000). In particular, Chung et al (2001) showed white matter local volume increase in the midbody, isthmus, and splenium of the corpus callosum in 28 normal subjects from 12 to 16 years. In our study, the age for the control group is 17.1 F 2.8, and for the autism group, it is 16.1 F 4.5 years ( Table 1).…”
Section: General Linear Modelsmentioning
confidence: 99%
“…While this overall goal may be impractical to accomplish at the moment, various prospective longitudinal efforts are underway. Within the methodological analysis of specific research groups, an initial glimpse of the form of the normal developmental trajectory for some anatomic structures can begin to be formed [Chung et al, 2001;Giedd et al, 1996;Giedd et al, 1999;Paus et al, 1999;Thompson et al, 2000]. Such valuable studies of their own right can easily be anticipated to be highly magnified in their significance when performed as a comprehensive, multi-site, longitudinal study utilizing a homogeneous analysis method.…”
Section: Discussionmentioning
confidence: 99%